Mental workload assessment among healthcare workers during pandemic COVID-19 at Hospital Tunku Azizah / Mohd 'Aizat Mohd Basari - Mohd 'Aizat, Mohd Basari (2020)
Workload is the amount of work an individual has to do. There is a distinction between the actual amount of work and the individual's perception of the workload. In addition, with current pandemic situation, definitely causes an increased workload among healthcare workers. Somehow, front-liners are doing their best in battling COVID-19 to protect publics from any adverse effects by this aggressive identified Coronavirus. The purpose of this study is to determine level of mental workload and its relationship on mental health status and job satisfaction among healthcare workers. Scope of this study involving medical laboratory workers in Pathology Department Hospital Tunku Azizah. Here, 85 workers from this department has been recruited as study subjects. This is a cross-sectional quantitative descriptive study using questionnaire. Research tools used for this questionnaire are CarMen-Q, DASS-21 and Job Satisfaction Survey (JSS). Questionnaire conducted via Google Form an analysed by SPSS-21 software. Mental workload are the independent variable of this study while the dependent variables are mental health status (depression, anxiety and stress) and job satisfaction. Data were analyses using descriptive statistics (percent, mean and standard deviation) and inference statistics (correlation). The findings of this study show Pathology Department workers are burdened with high mental workload with at least M=54.23, SD= 12.193. In this context, mental workload dimensional was found to have a significant correlation on mental health status and job satisfaction level among health workers. To conclude, this study has proven that healthcare workers are experiencing high mental working and have significant effects on their mental health status and their job satisfaction. Sets of strategies managing high level mental workload in Pathology Department need to be implemented